Pelatihan Pemanfaatan Media Sosial Sebagai Sarana Pembelajaran di Era Digital pada Guru-Guru SMP di Kecamatan Gunung Sugih Lampung Tengah: Pengabdian - Yustina Sri Ekwandari; Ema Agustina; Rinaldo Adi Pratama; Valensy Rachmedita; Aprilia Triaristina (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this community service activity is to improve teachers' knowledge about the use of social media as a learning tool in the digital era. Social media is an online platform that allows interaction, information sharing, and independent content creation, such as blogs, social networks, wikis, forums, and even virtual worlds. Many individuals utilize open social media platforms like Instagram, Facebook, Line, and Twitter to expand their reach and increase interaction. This activity uses training methods or direct mentoring for teachers in Gunung Sugih District, Central Lampung Regency. It is hoped that this activity will improve teachers' ability to utilize social media as a learning tool in the classroom, so that students become more enthusiastic and easily understand the material. The results of the activity showed high enthusiasm from the participants from beginning to end. This is evidenced by an increase in the average score from 67.0 in the pre-test to 78.8 in the post-test, an increase of approximately 17.6%. These findings indicate that the training went smoothly and was effective in improving teachers' understanding of the use of social media in learning in the digital era.